13 gifts [compact disc, unabridged] - Mass, Wendy, 1967- (Scholastic Audio, 2011)
Shortly before her thirteenth birthday, shy and withdrawn Alyssa is sent to stay with her aunt, uncle, and cousin in her parents' hometown of Willow Falls, where she makes friends and becomes involved with an elderly buyer and seller of collectibles, who seems to be trying to give Alyssa some kind of mysterious message.